A technical-economic analysis of the Eco Plus Gasoline introduction in the fuel market in Ecuador - Paredes Valencia, Milton Alejandro (2024)
This work conducted an exhaustive technical-economic analysis of introducing Eco Plus 89 gasoline in the Ecuadorian fuel market. The study was based on a bibliographic review of previous research and on obtaining marketing values for this fuel that allowed the evaluation of consumption, technical parameters, and prices in the Ecuadorian fuel market. Eco Plus 89 gasoline consumption growth was observed, reflecting a significant consumer demand and preference increase. Furthermore, from a technical point of view, this Eco Plus 89 gasoline demonstrates superior performance in terms of power and torque compared to its subsidized counterparts (Extra and Ecopaís gasoline), thanks to its higher-octane number. From an environmental perspective, Eco Plus 89 fuel offers notable advantages, including greater fuel efficiency and lower sulfur concentration, which reduces harmful emissions. Regarding market prices, Eco Plus 89 gasoline follows a similar trend to Super gasoline and has experienced a decrease in the last year, establishing itself as a competitive option with an average cost of $0.94 less per gallon than Super gasoline. Finally, a hypothetical case based on accurate data demonstrates that a vehicle that uses Eco Plus 89 gasoline consumes less fuel to travel the same distance than Extra or Ecopaís fuel, generating environmental benefits and maintaining a similar or even monthly fuel cost lower. As a result of this study, two critical recommendations are made: the experimental validation of the data and the promotion of fuels with ethanol blends in Ecuador to further improve performance and sustainability in the fuel market.